Orthodoxy versus heterodoxy: Inflation, unemployment, growth, profit - Carlos Manera (The European Association for Banking and Financial History (EABH), 2015)
Institutions like the IMF, the ECB and many finance ministries and private banks in the world's richest countries are sending out unequivocal calls for strict control of prices to be addressed urgently, given their intrinsic relationship with how the budget deficit and government debt evolve. These messages allow very little room for nuances or interpretations, stating categorically that price stability is the essential factor that guarantees economic growth and therefore plays a key role in enabling countries to achieve good living standards. Nevertheless, inflation, which nobody doubts needs to be kept under control, requires a much deeper analysis to avoid over-mechanical, over- simplistic applications for the present situation. We mustn't fall into what Paul Samuelson called basing economic policy on "shibboleths" - that is, hard and fast slogans that take over serious, thoughtful discussion and exchange of opinions. Especially since in economics slogans become hallmarks that are constantly repeated, and this repetition gets in the way of the obvious truth. This trend has led to the sale of intellectual products with no scientific backing. A case in point is David H. Fischer's book on prices. Addressing business leaders, he asserts categorically that econo mic cycles and crises have ended, but the actual economic events have disproved this. As Robert Solow warns, there is not one set of laws of economics applicable to all times and all places, and the part of e conomics that is not dependent upon economic history and the social context is very small and of little interest.
Keywords: B50; B41; N1; 330; inflation; economic growth; heterodox view